Locating Unreported Leaks with Modelling Tools and Pressure Monitoring: a Case Study - Ribeiro, Luisa (2020)
Water losses are a major concern for water companies, mostly due to their economical, technical, social and environmental negative impacts. Unreported leaks are a major cause of water losses in water distribution networks (WDNs) and they are difficult to locate, particularly in plastic pipes, large diameters and low pressure conditions. The location of these leaks is very time consuming and requires specialized human resources, using sophisticated and costly acoustic equipment. The use of modelling and optimization tools, supported by flow and pressure measurements, is showing to be a challenging alternative to the traditional procedure. This paper presents the application of the methodology proposed in Ribeiro L. S., 2012; Ribeiro L. S., 2015; Sousa, 2015 to a real WDN, highlighting the major difficulties faced when dealing with real world conditions, namely gathering and checking data, and building and calibrating the water distribution model. The results obtained in this case study show that this approach is very promising, encouraging future applications and developments